2023
DOI: 10.1002/chem.202301894
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring‐Group Participation by C‐2 Acyloxy Groups: Influence of the Nucleophile and Acyl Group on the Stereochemical Outcome of Acetal Substitution Reactions

Abstract: A single acyloxy group at C‐2 can control the outcome of nucleophilic substitution reactions of pyran‐derived acetals, but the extent of the neighboring‐group participation depends on a number of factors. We show here that neighboring‐group participation does not necessarily control the stereochemical outcome of acetal substitution reactions with weak nucleophiles. The 1,2‐trans selectivity increased with increasing reactivity of the incoming nucleophile. This trend suggests the intermediacy of both cis‐fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The relative stability of the cations was assessed through a density functional theory (DFT) protocol, in which the conformational energy landscape (CEL) maps for these cations were generated. , This method maps the energy of the glycosyl cations as a function of their shape by probing the complete conformational space that these cations can occupy. We plotted the relative stability of the dioxanium ion versus the oxocarbenium ion for the glucosyl (Figure a) and the mannosyl (Figure b) cations.…”
Section: Resultsmentioning
confidence: 99%
“…The relative stability of the cations was assessed through a density functional theory (DFT) protocol, in which the conformational energy landscape (CEL) maps for these cations were generated. , This method maps the energy of the glycosyl cations as a function of their shape by probing the complete conformational space that these cations can occupy. We plotted the relative stability of the dioxanium ion versus the oxocarbenium ion for the glucosyl (Figure a) and the mannosyl (Figure b) cations.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of these reactions emerged during stimulating conversations with the group of Professor Codée. 105 Taken together, we concluded that, just as for the systems with remote substituents (Scheme 45 and Figure 21 ), the presence of an intermediate is not sufficient to say that it is responsible for the stereochemistry of the reaction.…”
Section: Neighboring-group Participation Is Not As Simple As It Seemsmentioning
confidence: 85%
“…Acyloxy groups can engage in participation, but this participation, like in the case of the sulfur system, depended upon the nature of the nucleophile. 105 With relatively weak alkene nucleophiles, the reaction favored the 1,2- cis product (e.g., 246 in Scheme 49 ), but the expected 1,2- trans product became the major product as the nucleophile became more reactive and more hindered (Scheme 49 ). The correlation between reactivity and stereoselectivity was also observed with oxygen nucleophiles (Scheme 50 ).…”
Section: Neighboring-group Participation Is Not As Simple As It Seemsmentioning
confidence: 99%